Disturbance wave development in two-phase gas-liquid upwards vertical annular flow - Zhao,Y; Markides,CN; Matar,OK; Hewitt,GF (International Journal of Multiphase Flow, 2013)
Disturbance waves are of central importance in annular flows. Such waves are characterised by their large amplitudes relative to the mean film thickness, their high translation velocities relative to the mean film speed, and their circumferential coherence. The present paper is concerned with the existence, development and translation of disturbance waves in upwards, gas–liquid annular flows. Experiments are described, which featured simultaneous high-frequency film thickness measurements from multiple conductance probes positioned circumferentially and axially along a vertical pipe, these measurements were aimed at studying the three-dimensional development of these interfacial structures as a function of distance from the tube inlet. From the results, it is found that disturbance waves begin to appear and to achieve their circumferential coherence from lengths as short as 5–10 pipe diameters downstream of the liquid injection location; this coherence gradually strengthens with increasing distance from the inlet. It is further shown that the spectral content of the entire interfacial wave activity shifts to lower frequencies with increasing axial distance from the inlet, with the peak frequency levelling off after approximately 20 pipe diameters. Interestingly, on the other hand, the frequency of occurrence of the disturbance waves first increases away from the inlet as these waves form, reaches a maximum at a length between 7.5 and 15 pipe diameters that depends on the flow conditions, and then decreases again. This trend becomes increasingly evident at higher gas and/or liquid flow-rates. Both wave frequency measures increase monotonically at higher gas and/or liquid flow-rates.